(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
This study examines the impact of the typology and severity of occupational accidents on the costs associated with medical care in manufacturing companies in Zone 8 of Ecuador. It analyzes the importance of accident prevention and occupational safety management in reducing these costs and improving the health and well-being of workers. A quantitative investigation was carried out that included the collection of data on accidents, medical costs and other related factors. The results reveal the significant relationship between accident typology and medical care costs, highlighting the importance of prevention and occupational safety management.